2009
DOI: 10.1002/pola.23814
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of phenothiazylene vinylene‐based polymers: New organic semiconductors for field‐effect transistors and solar cells

Abstract: A series of new phenothiazylene vinylene‐based semiconducting polymers, poly[3,7‐(4′‐dodecyloxyphenyl)phenothiazylene vinylene] (P1), poly[3,7‐(4′‐dodecyloxyphenyl)phenothiazylene vinylene‐alt‐1,4‐phenylene vinylene] (P2), and poly[3,7‐(4′‐dodecyloxyphenyl)phenothiazylene vinylene‐alt‐2,5‐thienylene vinylene] (P3), have been synthesized via a Horner‐Emmons reaction. FTIR and 1H NMR spectroscopies confirmed that the configurations of the vinylene groups in the polymers were all‐trans (E). The weight‐averaged mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Polymers and organic molecules containing phenothiazine or their derivatives have attracted considerable interest on the account of their unique electro-optical properties, which makes these molecules potential candidates for diverse applications in photoluminescence, chemiluminescence, 16 and energy as well as data storage devices. Recently, phenothiazine polymers have been used in polymer lightemitting diodes, [16][17][18][19] organic field-effect transistors, [20][21] and organic solar cells. 22,23 In this study, incorporation of a bulky substituent like tricyclic phenothiazine unit into rigid PI backbone was carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Polymers and organic molecules containing phenothiazine or their derivatives have attracted considerable interest on the account of their unique electro-optical properties, which makes these molecules potential candidates for diverse applications in photoluminescence, chemiluminescence, 16 and energy as well as data storage devices. Recently, phenothiazine polymers have been used in polymer lightemitting diodes, [16][17][18][19] organic field-effect transistors, [20][21] and organic solar cells. 22,23 In this study, incorporation of a bulky substituent like tricyclic phenothiazine unit into rigid PI backbone was carried out.…”
Section: Introductionmentioning
confidence: 99%
“…FCPA did not show any peak in XRD, suggesting that FCPA is completely amorphous (Figure 6). 51 The differential scanning calorimetry (DSC) of FCPA (Figure S13, Supporting Information) revealed that the melting point of FCPA was 48.7 °C and the absence of the crystallization peak on the cooling cycle indicated that the compound is amorphous and explained its film-forming property. This observation is in contrast to the previous AIE molecules reported with phenothiazine and bulky aromatic groups.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…They are also characterized by high electrical and thermal stability, with high excellent electro-optical characteristics in devices. [51][52][53] Phenothiazine was used as electron donor, with benzothiadiazole, possessing a robust electron affinity as electron acceptor, and thiophene with rich electrons linked to each end to increase p-conjugation efficiency. This provides a design of a basic molecular structure, affording a low band gap polymer.…”
Section: Introductionmentioning
confidence: 99%